Literary geography : an encyclopedia of real and imagined settings - Houston, Lynn Marie (Greenwood, 2019)
This is an authoritative guide for students, teachers, and avid readers who seek to understand the importance of setting in interpreting works of literature, including poetry. By examining how authors and poets shaped their literary landscapes readers will discover historical, political, and cultural context hidden within the words of their favorite reads. The alphabetically arranged entries provide easy access to analysis of some of the most well-known and frequently assigned pieced of literature and poetry. Entries begin with a brief introduction to the features piece of literature and then answer the questions: "How is literacy landscape used to shape the story?" and "How is the literary landscape imbued with the geographical, political, cultural, and historical context of the author's contemporary world, whether purposeful or not?" Pop-up boxed provide quotes about literary landscapes throughout the book, and an appendix takes a brief look at the places writers congregated and that inspired them. A comprehensive scholarly bibliography of secondary sources pertaining to mapping, physical and cultural geography, ecocriticism, and the role of nature in literature rounds out the work.